Validating Homogryllacris eremna and establishing H. unicolor as a synonym of H. anelytra, with description of the female of H. ascenda (Orthoptera: Gryllacrididae) - Duan, Yueting; Duan, Yanhao; Liao, Haishu; Shi, Fuming (Zootaxa, 2026)
In a recent study by Duan et al. (2025), the new species Homogryllacris eremna was proposed and H. unicolor Lu, Zhang & Bian, 2022 was suggested as a synonym of H. anelytra Shi, Guo & Bian, 2012. However, as the corresponding descriptions and diagnoses were provided solely in supplementary files, these names fail to meet the availability requirements of the International Code of Zoological Nomenclature (ICZN). To resolve it, this study provides the necessary information through formal publication to validate these taxonomic acts. First, a complete morphological description is provided and type specimens are designated for H. eremna, thereby making the name available. Second, based on integrated molecular and morphological evidence, H. unicolor is formally established as a synonym of H. anelytra. Additionally, the female of H. ascenda Shi, Guo & Bian, 2012 is reported and described for the first time.